Comparison of the homodynamic effects of Nesdonal and Propofol in patients under electroconvulsive therapy - Seddighi, Afsoun; Nikouei, Amir; Seddighi, Amir Saied (International Clinical Neuroscience Journal, 2017)
Background: General anesthesia is a safe method for induction of electroconvulsive therapy (ECT) in patients suffering from psychiatric disorders. We aimed to compare the hemodynamic effects of Nesdonal and propofol as induction agents for ECT. Methods: This semi-experimental study was performed on 84 patients with confirmed diagnosis of psychiatric disorders, who underwent ECT at Shohada Tajrish hospital in 2016. After randomization, each patient either received Nesdonal or propofol for induction of anesthesia. Hemodynamic changes of mentioned anesthetic agents were recorded and evaluated during ECT, including systolic and diastolic blood pressure, heart rate, seizure duration related to the procedure and recovery from sleep. Statistical analysis was performed using Student t test and Friedman test. Results: There were 50 men and 34 women among included patients. The mean and standard deviation (SD) of age of patients in Nesdonal group in female and male were 40.5 ± 13.4 years and 30.2 ± 13.5 years, respectively. Data for propofol group was 36.5 ± 20.9 years and 25.7 ± 7.7 years for female and male patients, respectively. Nesdonal offered a superior hemodynamic stability during the procedure, and seizure duration has decreased with Nesdonal compared with propofol. However, patients who underwent propofol for their anesthesia recover faster from sleep, while systolic and diastolic blood pressure of this group were higher than Nesdonal group (P < 0.0001). Conclusion: Considering better hemodynamic stability, it seems that Nesdonal is better than propofol for induction in ECT.